Lesbian, gay, bisexual, and transgender aging : research and clinical perspectives - Kimmel, Douglas C.; Rose, Tara, Dr; David, Steven, 1967- (Columbia University Press, 2006)
Lesbian, Gay, Bisexual, and Transgender Aging brings together cutting-edge research, practical information, and innovative thinking regarding the characteristics and processes of aging among lesbian, gay, bisexual, and transgender individuals. Written by experts in the field, the book covers a range of subjects and provides a comprehensive knowledge base for practitioners, students, and researchers. Contributors address topics such as sexuality, relationships, legal issues, retirement planning, physical and mental health, substance abuse, community needs, gay and lesbian.